EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) BERBASIS MIND MAPPING DITINJAU DARI GAYA BELAJAR SISWA KELAS VII SMP NEGERI SE-KABUPATEN PACITAN TAHUN PELAJARAN 2013/2014 - Wahyu Utomo; Mardiyana Mardiyana; Tri Atmojo Kusmayadi (Jurnal Pembelajaran Matematika, 2015)
Abstract: The objective of the research was to determine the influence of learning models toward mathematics achievement viewed from the students’ learning styles. The compared learning models were mind mapping based on Numbered Head Together (NHT) cooperative learning model, NHT cooperative learning model and direct instruction model. The type of the research was a quasi-experimental research. The population was the students of junior high school in Pacitan regency on academic year 2013/2014. The size of the sample was 237students consisted of 79 students in the first experimental group, 80 students in the second experimental group and 78 students in the control group.  The  instruments  used  were  mathematics achievement test and learning styles questionnaire. The data was analyzed using two way analysis of variance with unequal cell frequencies. The conclusions of the research were as follows. (1) mind mapping based on NHT cooperative learning model gives better mathematics achievement than NHT cooperative learning model and direct instruction model, NHT cooperative learning model gives better mathematics achievement than direct instruction model. (2) The visual learning style students have better mathematics achievement than the auditory learning style students and the kinaesthetic learning style students, the auditory learning style students have better mathematics achievement than the kinaesthetic learning style students. (3) For all learning models, the visual learning style students have better mathematics achievement than the auditory learning style students and the kinaesthetic learning style students, the auditory learning style students have better mathematics achievement than the kinaesthetic learning style students. (4) For all the students’ learning styles, mind mapping based on NHT cooperative learning model gives better mathematics achievement than NHT cooperative learning model and direct instruction model, NHT cooperative learning model gives better mathematics achievement than direct instruction model.Keywords: NHT, mind mapping, learning styles